공공 공간 가림막의 레이아웃 디자인 표현 형식의 연구 - 하오동민; Haodongmin; 이홍; Lee Hong; 이성필; Lee Sung Pil (기초조형학연구, 2018)
2000년대 이후 국내에서 공공디자인 사업이 활발하게 이루어졌으며, 여러 국가에서는 도시 미관을 저해시키는 설치물 중 공사장 가림막의 디자인을 개선하고 있다. 서울 곳곳에서 공공공간인 공사장 가림막에 다양한 디자인 작업들이 적용되었고, 이는 도시의 미관 및 매력을 향상시켰으며, 오늘날 공사장 가림막이 하나의 디자인 영역으로 자리매김하고 있다. 따라서 본 연구는 2009년 이후에 설치된 국내·외 공공공간 공사장 가림막 12개 사례를 분석하였다. 국내 사례는 한국 101파인컬렉션, 경복궁 광화문, 서울시청 신관 현장, 장인의 손, 거리미술관, 신세계백화점 본관을, 국외 사례는 미국의 Walking Man과 The East Cut, IBM, 중국의 The　New　Wave, 영국의 Rambert Dance, 일본의 시부야구 가림막이다. 사례분석 결과, 국내 공사장 가림막의 특성은 주로 기능성과 심미성을 반영하며, 이러한 특성을 효과적으로 표현하기 위하여 사진 및 일러스트레이션과 다양한 색상을 활용하는 것으로 나타났다. 이를 통해 국내 사례는 통일과 균형 이루어 서로 조화롭게 어울림을 알 수 있었다. 국외 공사장 가림막의 특성은 주로 기능성과, 심미성, 테마성을 반영하였으며, 이를 효과적으로 표현하기 위해 사진 및 일러스트레이션 및, 다양한 색상을 사용하였다. 이를 통해 국외 사례는 통일과 균형, 변화와 강조가 중점적으로 나타났다. 종합적으로, 국내·외 모든 사례에서 대부분 기능성과 심미성, 사진 및 일러스트레이션, 색상, 통일을 중요하게 다룸을 알 수 있었다. 또한 공사장 가림막의 설치 목적과 주제에 맞는 테마성, 타이포그래피와 여백 등을 활용하여 변화 및 강조를 표현하였다. 따라서 본 연구 결과에서 나타난 공사장 가림막의 특성을 참고하여 향후 국내 공사장 가림막 설치 시 더욱 다채롭고 창의적인 가림막 디자인 표현에 도움이 될 것이며, 이는 해당 도시의 미관과 도시 환경의 심미성 형성에 기여할 수 있을 것이다. Since the 2000s, public design projects have been actively carried out in the domestic, many countries has been improved the design of the construction fence among the installations that hinder the beauty of the city. Various design works had applied to the construction fence of the public space in places of Seoul, which has improved the beauty and charm of the city, today the construction fence is positioning a one design area. Therefore this study analyzed 12 cases of domestic and foreign public space construction fence installed after 2009. Domestic cases is Korea 101 fine collection, Gwanghwamun Gate of Gyeongbokgung Palace, Shingwan place of Seoul Metropolitan Government, hands of craftsmen, art museum of streets, main building of shinsegae department store, foreign cases is Walking Man and The East Cut and IBM in the United States, The　New　Wave in China, Rambert Dance in the United Kingdom, Shibuya fense in Japan. Case analyzed result, feature of domestic construction fence reflect mainly functionality and aesthetic, it has been shown that picture and illustrations and various colors are used to effectively express these characteristics. Through this, domestic cases could know that unification and balance harmonized with each other. Feature of foreign construction fence reflect mainly functionality and aesthetic and theme, it has been shown that picture and illustrations and various colors are used. Through this, foreign cases could see mainly that unification and balance and variance and emphasize. Overall, in all cases both domestic and foreign were able to see that most of the functionality and aesthetic and picture and illustrations and colors and unification were important. In addition, the theme and typography and margin suitable for the install purpose and subject of the construction fence were used to express variance and emphasis. Therefore by referring to the characteristics of the construction fence shown in this study, it will help to express more colorful and creative fence design in the future when installing the curtain of the domestic construction fence, which will contribute to the aesthetics of the city and the aesthetics of the urban environment.